HISTORICAL PERSPECTIVES OF THE STUDY OF ENANTIOSEMY IN ENGLISH, RUSSIAN AND UZBEK LINGUISTICS (Scientific journal of the Fergana State University, 2023)
The article offers a general overview on the history of the enantiosemy development in three languages: Russian, Uzbek and English. In this article the authorgives various linguists’ points of view regarding the essence of enantiosemy phenomenon and its types.